Hukum dan Investasi: Aspek Perlindungan Hukum oleh Otoritas Jasa Keuangan bagi Investor Pasar Modal - Hasbuddin Khalid (LPPM Universitas Ekasakti Padang, 2023)
The increasing number of investors in the Indonesian capital market is often not accompanied by sufficient legal protection for investors. With the presence of the Financial Services Authority (OJK) substituting the role of BAPPEPAM, it is hoped that the aspect of legal protection for investors will be more optimal. This study aims to analyze the legal protection provided by OJK to investors on the Indonesia Stock Exchange, both in terms of form, implementation, and effectiveness. This study uses empirical legal research methods by examining secondary data supported by primary data through interviews. The results of the analysis are presented using a qualitative-descriptive technique. The results of this study indicate that OJK facilitates three forms of legal protection for investors: first, pre-emptive protection in the form of financial literacy education to investors; second, preventive protection in the form of licensing authority for securities as well as regulation and supervision of financial services; and third, repressive protection through a series of authorities in the field of justice. However, based on the facts, several forms of OJK legal protection are deemed ineffective due to a number of factors, including legal structure, legal substance, and legal culture.